Learning the Right Attitude and Skills to Grow as a Future Leader : Mempelajari Sikap dan Keterampilan yang Tepat untuk Tumbuh sebagai Pemimpin Masa Depan - Paulus Yulius Fanggidae; Kevin Mulyono Sudrajat; Martha Felista (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
This Community Service (PKM) activity aims to improve the leadership competency of prospective student council (OSIS) administrators at SMK Tzu Chi Cengkareng through the training "Learning the Right Attitude and Skills to Grow as a Future Leader." The background of the activity is based on the importance of effective leadership amidst global change and limited internal school resources for developing non-technical skills. This training focuses on instilling ethics, a sense of ownership, responsibility, teamwork, and effective communication. The implementation method involves interactive lectures, group discussions, and simulations. Pre-test and post-test evaluation results from 25 respondents showed a significant increase in knowledge comprehension (from 30% to 86% correct answers) and a positive attitude change (a 56% increase in positive attitude scores). The conclusion indicates that this PKM successfully achieved its goal of developing more reflective, collaborative, and responsible young leaders. Therefore, this training model is recommended for leadership development programs in schools.